COHESION AND COHERENCE IN WRITTEN TEXTS OF HEALTH MEDICAL LABORATORY STUDENTS - Fiki Setiawan; Taiman Taiman (University of Kuningan, 2021)
Good writing, which is cohesive and coherent, must pay attention to the relationship between sentences. Cohesive and coherence are essential textual components to create the organized and comprehensiveness of the texts. This research aims to identify the use of cohesion devices and coherence made by the students in their writing texts. This study applied a descriptive qualitative method. The study's object was eight explanation texts written by linguistic learning style students of Health Medical Laboratory An Nasher Cirebon in the academic year of 2019/2020, who were taking English subjects. The data collected through documentation. The qualitative analysis was performed to explore the results. The result revealed that reiteration among all forms of grammatical and lexical cohesion, which occurs 207 times or 47.15 percent, is the most common form. The reference that appears 124 times or 28.25 percent follows. Collocation is the third position, which happens 60 times or 13.67%. Conjunction, meanwhile, occurs 44 times or 10.02 percent, replacement appears 3 times or 0, 68 percent and ellipsis appears 1 times. In terms of macro level coherenece, the results showed that additives were mostly used in student texts. followed by causal, temporal and last was adversative It concluded that the students to be competing well in producing cohesion and coherence in their writing texts. They use all kinds of coherence in their written text with only one ellipsis, and they apply all kinds of coherence in their written text.Keywords: Cohesion; coherence; discourse